SOCIALIZATION AND TRAINING OF UTILIZATION LEARNING MEDIA BASED ON LEARNING MANAGEMENT SYSTEM (LMS) WITH MOODLE FOR JUNIOR HIGH SCHOOL TEACHERS - Lastama Sinaga; Widia Ningsih; Mariati Purnama Simajuntak; Aristo Hardinata (Pelita Eksakta, 2021)
Socialization and training of the use of learning media based on learning management system (LMS) with moodle for junior high school teachers at Methodist 8 Medan aims to improve teachers' knowledge and skills in integrating Information Technology and Communication (ICT) into interactive, interesting and fun online learning. Moodle is a software application produced for dynamic learning activities based on technology, internet and websites. The methods that used for implementing this Community Partnership Program are socialization and training which begin with preliminary observations, analysis of learning problems and the needs of teachers and students. The next stage is the preparation of activities both from the partners and the team. The third and fourth stages are socialization and training on the use of learning media based on LMS by using the Moodle features. The result of this partnership program is that teaching materials such as power point presentation, learning videos, assignments and quizzes/student worksheets have been created and uploaded by utilizing the features in Moodle.